2013
DOI: 10.1159/000350488
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Human Leukocyte Antigen G Molecule Expression in Allogeneic Hematopoietic Stem Cell Transplantation: Good Predictor of Acute Graft-versus-Host Disease

Abstract: Background: Graft-versus-host disease (GVHD) remains a main complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Human leukocyte antigen G (HLA-G) is a non-classical class I molecule exerting multiple immunoregulatory functions. The aim of this study was to explore the relationship between soluble HLA-G (sHLA-G) and GVHD after allo-HSCT. Methods: The sHLA-G levels were examined using enzyme-linked immunosorbent assay in patients with hematological malignancies (n = 106) before transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…Literature data point to the important role of HLA-G molecule in the occurrence of GVHD and to the correlation between HLA-G level in patients' blood serum following allotransplantation and the severity of GVHD. Liu et al [20] confirmed that HLA-G5 level may play the role of a prognostic factor for the development of GVHD and the clinical course of this reaction.…”
Section: Discussionmentioning
confidence: 94%
“…Literature data point to the important role of HLA-G molecule in the occurrence of GVHD and to the correlation between HLA-G level in patients' blood serum following allotransplantation and the severity of GVHD. Liu et al [20] confirmed that HLA-G5 level may play the role of a prognostic factor for the development of GVHD and the clinical course of this reaction.…”
Section: Discussionmentioning
confidence: 94%
“…In the first 30 days after HCT, levels of the soluble G5, G6 and G7 proteins were significantly higher compared to pre-transplant levels; higher levels of soluble HLA-G proteins were found in patients without GVHD compared to lower levels in patients who developed grades II–IV acute GVHD 89 . Very intriguing data on the recovery of CD14 + HLA-G + cells in the plasma of healthy and transplant patients and the ability to antagonize the suppressive function of these cells through HLA-G blockade provide new information on the contribution of HLA-G-expressing monocytes in the immune response 87 .…”
Section: The Role For Major Histocompatibility Complex Resident Non-hmentioning
confidence: 86%
“…Although it has classically been considered that HLA-G expression is restricted to the maternal-fetal interface, the thymus, and the cornea, several recent studies have found increased levels of HLA-G in the plasma 8789 and in GVHD target organs in patients receiving allogeneic HCTs 87 . In the first 30 days after HCT, levels of the soluble G5, G6 and G7 proteins were significantly higher compared to pre-transplant levels; higher levels of soluble HLA-G proteins were found in patients without GVHD compared to lower levels in patients who developed grades II–IV acute GVHD 89 .…”
Section: The Role For Major Histocompatibility Complex Resident Non-hmentioning
confidence: 99%
“…Indeed, increased HLA-G5 levels on day 15 and on day 30 after HCST seem to be negatively correlated with the severity of aGvHD [109] suggesting HLA-G5 as a predictor of the occurrence and severity of aGvHD. This concept has been further sustained by the fact that high levels of HLA-G before and after allograft are indicative for good HCST outcome with respect to the occurrence of aGvHD.…”
Section: Hla-g and Transplantationmentioning
confidence: 99%